2006
DOI: 10.1177/0885066606290671
|View full text |Cite
|
Sign up to set email alerts
|

Use of Methylene Blue in Sepsis: A Systematic Review

Abstract: A systematic review of the literature was conducted to determine if the administration of methylene blue in humans improves hemodynamic status and/or outcome in patients with septic shock. Studies were identified from MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials database. The review included human studies of patients with septic shock treated with methylene blue in which hemodynamic variables or mortality rates were reported. An electronic form was used to extract items including stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
115
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 34 publications
(25 reference statements)
3
115
1
1
Order By: Relevance
“…Its pharmacologic mechanism of effect and previous descriptions in sepsis literature [15][16][17] support its use in vasodilatory shock from calcium channel blocker poisoning. Septic shock is associated with excess nitric oxide production which in turn stimulates soluble guanylyl cyclase (cGMP) to increase endothelial smooth muscle relaxation [15].…”
Section: Discussionmentioning
confidence: 59%
“…Its pharmacologic mechanism of effect and previous descriptions in sepsis literature [15][16][17] support its use in vasodilatory shock from calcium channel blocker poisoning. Septic shock is associated with excess nitric oxide production which in turn stimulates soluble guanylyl cyclase (cGMP) to increase endothelial smooth muscle relaxation [15].…”
Section: Discussionmentioning
confidence: 59%
“…Methylene blue has been used over the last several years as a treatment for intractable hypotension in anaphylaxis, sepsis, and vasoplegia from cardiopulmonary bypass during cardiac surgery [32][33][34][35]. Multiple case reports document the reversal of anaphylactic symptoms, including druginduced cardiac arrest and angioedema, after patients receive methylene blue [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, we report the need for a prolonged infusion of MB over a period of 120 hr in a patient with intractable septic shock. Previous research has demonstrated that MB may be efficacious in septic shock when given by intravenous bolus or short-term (B6 h) infusions, 3,4,9,11,[16][17][18] although a case report of a longer-term infusion of 44 hr has been described. 12 Despite standard treatment for septic shock with early goal-directed therapy, conventional vasopressors, including norepinephrine, epinephrine, and vasopressin, our patient responded only to the administration of MB.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] Little is known about the clinical utility, optimal dose, or duration of MB administration in patients with septic shock. The relatively few reports available on the use of MB in septic shock describe relatively short infusions.…”
Section: Résumémentioning
confidence: 99%